Increase in the risk of clopidogrel resistance and consequent TIMI flow impairment by DNA hypomethylation of CYP2C19 gene in STEMI patients undergoing primary percutaneous coronary intervention (PPCI) - Renan Sukmawan; Erick Hoetama; Siska Suridanda Danny; Astuti Giantini; Erlin Listiyaningsih; Vidya Gilang Rejeki; Amir Aziz Alkatiri; Isman Firdaus (Wiley, 2021)
Abstract Clopidogrel resistance is an important risk factor of ischemic event recurrence after optimal antiplatelet therapy. This study aims to investigate the role of CYP2C19 gene DNA methylation as one of the epigenetic factors for the risk of clopidogrel resistance in STEMI patients undergoing PPCI. ST‐segment elevation myocardial infarction (STEMI) patients undergoing PPCI were pretreated with clopidogrel, and their platelet function was measured using VerifyNow™ assay. The criteria for high on‐treatment platelet reactivity (HPR) were defined according to the expert consensus criteria (PRU >208). DNA methylation of the CYP2C19 gene was performed using bisulfite genomic sequencing technology. Furthermore, clinical, laboratory, and angiographic data including TIMI flow were collected. Among 122 patients, clopidogrel resistance was found in 22%. DNA methylation level percentage was lower in the clopidogrel resistance group (76.7 vs. 88.8, p‐value .038). But, the <50% methylation group was associated with increased risk of clopidogrel resistance (OR =4.5, 95%CI =2.1-9.3, p‐value = .018). This group was also found to have suboptimal post‐PCI TIMI flow (OR =3.4 95%CI =1.3-8.7, p‐value =.045). The lower DNA methylation level of the CYP2C19 gene increases the risk of clopidogrel resistance and subsequent poorer clinical outcome.